Are central banks to blame? Monetary policy and bank lending behavior - Michail, Nektarios A.; Savva, Christos S.; Koursaros, Demetris (My University, 2021)
This paper tests the conjecture that easy money policies of central banks, that is setting low rates for long, are responsible for the excess risk-taking behavior that led to the global financial crisis. If the conjecture holds then policy rate shocks should have persistent effects on bank behavior either through the bank lending or the risk-taking channel. Using data for the period prior to the global financial crisis, and a shock persistence methodology, we find that the policy rate has only limited idiosyncratic effects on bank lending growth and no effect on credit risk.
Keywords: Bank lending; Euro area; Interest rate; Monetary policy; Persistence